Determinants that Affect Females’ Attitudes Toward Online Shopping in the Western Region of Saudi Arabia - Saeed Alshehri, Manal; Azman Ali, Noor; Sidek, Shafie; Hwa, Jacky Cheah Jun (Advances in Social Sciences Research Journal, 2022)
This research aims to determine the factors that influence females’ attitude toward online shopping in Saudi Arabia. The potential and main theory that is selected for this study is the Theory of Acceptance Model (TAM) which studies online shopping acceptance of new technology through two important variables which are perceived ease of use and perceived usefulness. Furthermore, this research has included the factors of site quality, site credibility, and customer fashion lifestyle. The self-administrated method has been used to distribute the questionnaire for the respondents, who are selected by utilizing the judgement sampling technique. 320 questionnaires were valid for analysing. SPSS and Smart PLS software have been employed for analysing the data of study. The finding of the present pointed out that perceived ease of use, site quality, and customer fashion lifestyle have a significant positive relationship with females’ attitude toward online shopping. In contrast, usefulness and site credibility were not statistically significant. This study has significantly contributed to literature on the shopper’s attitude toward online shopping. On the other hand, the findings of this study represented a guideline for e-retailers in Saudi Arabia to increase and maintain online shoppers for the long term and compete with other competitors. Finally, study limitations are discussed, and future study directions are proposed.